Download presentation

Presentation is loading. Please wait.

Published byAngie Pagan Modified about 1 year ago

1
Homework – Chapter 1 作業解答

2
Problem 1 Given the Fibonacci number as 1 2 3 5 8 13 21 34… where the next Fibonacci number will be the sum of its previous two Fibonacci number. –Example: The number of 8 is the sum of 3 and 5. The next number will be 55 since it is the sum of 21 and 34.

3
Problem 1 1.Write a recursive algorithm to generate the Fibonacci number N. int Fibonacci (int N) { if (N <= 2) return N; return Fibonacci(N-1) + Fibonacci(N-2); }

4
Problem 1 2.Write a non-recursive algorithm using loop structure to generate the Fibonacci number N. int Fibonacci2 (int N) { if (N <= 2) return N; Let N1 = 1, N2 = 2, Total = 0; for (i = 3 to N) { Total = N1 + N2; N1 = N2; N2 = Total; } return Total; }

5
Problem 1 3.Discuss the execution efficiency of these two programs. –The process of the recursive Fibonacci() can be illustrated by the following tree structure. –Space complexity of Fibonacci(): At most N-1 stack frames (the depth of the tree) are pushed into function call stack when Fibonacci() is called. Therefore, the complexity is O(N). –Time complexity of Fibonacci(): Therefore, the time complexity depends on how many nodes the tree has, which is O(2 N ).

6
–Space complexity of Fibonacci2(): Only a fix number of automatic variables are required. Therefore, the complexity is O(1). –Time complexity of Fibonacci2(): The for-loop runs in N-2 times. Its body perform addition in O(1) for each iteration. Therefore, the total computing time is O(N). Conclusion: –Fibonacci2() is more efficient than Fibonacci(). Its space complexity and time complexity are relatively lower.

7
Problem 2 Ordering by asymptotic growth rates: (A)log(n!) (B)4 logn (C)(n-1)! (D)n ． 2 n (E)(logn) logn. –Please write computation!

8
Solution (A)log(n!) log(n!) < log(n n ) = O(n logn) (B)4 logn Let S = 4 logn logS = log4 logn = log2 2logn = 2logn = logn 2 ∴ S = n 2 = O(n 2 ) (C)(n-1)! = O(n!) (D)n ． 2 n < 2 n ． 2 n = 2 2n = O(2 n ) ∴ (A) < (B) < (D) < (C)

9
Solution (E)(logn) logn Let S = (logn) logn log S = (logn)(loglogn) = log(n loglogn ) S = n loglogn < n logn < 2 n 2 n is growing faster than n logn. ∴ (A) < (B) < (E) < (D) < (C) nn logn 2n2n 112 10 1024 10010 4 2 100 ………

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google